EDUKASI SWASEMBADA AIR UNTUK MASYARAKAT PADUKUHAN DUKUH MELALUI FORUM GROUP DISCUSSION - Trisnaning, Paramitha Tedja; Widiastuti, Dyah Suwarti; Fatimah, Fatimah (Universitas Mataram, 2025)
Clean water is a vital basic need in community life. In Dusun Dukuh, access to clean water still faces various challenges such as uneven distribution, unsecured quality, and low public awareness of the importance of sanitation. To address these issues, a Focus Group Discussion (FGD) was initiated as a participatory platform for local youth. The FGD activities involved Karang Taruna Dukuh Tegal, community leaders, the village government, and other relevant parties. Through joint discussions, clean water issues were mapped: from sources, distribution channels, management, to water usage habits. The purpose of this study was to analyze how the forum can strengthen the role of youth in clean water access solutions, increase public awareness, and identify effective operational strategies. The method used was a qualitative approach with observation, in-depth interviews, and documentation during the FGD process. The results showed that the FGD increased solidarity among youth, generating local ideas such as building community wells, managing donated distribution equipment, and promoting cleanliness campaigns. However, obstacles such as limited funds and lack of institutional support still need to be addressed. Conclusion: The Focus Group Discussion Forum (FGD) is an effective tool for Karang Taruna Dukuh Tegal in fighting for access to clean water. However, intervention from policymakers and resource allocation are needed for the initiative to be sustainable.